Participation of FACTS in stabilizing DFIG with crowbar during grid fault based on grid codes - Okedu, K.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2011)
This paper investigates the effect of connecting FACTS (Flexible AC Transmission System) device such as a STATCOM (Static Synchronous Compensator) to the point of common coupling (PCC) of a wind farm composed of DFIG. Simulation results show that a FACTS device can effectively enhance the performance of the DFIG, when it is disconnected by the crowbar switch during grid fault by providing additional reactive power to the system, thus improving the voltage instability performance of the DFIG and the wind farm as well.